-4(2q-7)+6q-7=

Simple and best practice solution for -4(2q-7)+6q-7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(2q-7)+6q-7= equation:


Simplifying
-4(2q + -7) + 6q + -7 = 0

Reorder the terms:
-4(-7 + 2q) + 6q + -7 = 0
(-7 * -4 + 2q * -4) + 6q + -7 = 0
(28 + -8q) + 6q + -7 = 0

Reorder the terms:
28 + -7 + -8q + 6q = 0

Combine like terms: 28 + -7 = 21
21 + -8q + 6q = 0

Combine like terms: -8q + 6q = -2q
21 + -2q = 0

Solving
21 + -2q = 0

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-21' to each side of the equation.
21 + -21 + -2q = 0 + -21

Combine like terms: 21 + -21 = 0
0 + -2q = 0 + -21
-2q = 0 + -21

Combine like terms: 0 + -21 = -21
-2q = -21

Divide each side by '-2'.
q = 10.5

Simplifying
q = 10.5

See similar equations:

| X-14=28+x | | X(x+1)=0.75 | | 89-5x=31x+21 | | 5x+2(x-3)=-15 | | 6(x-6)+6=8x+6 | | 46-4x=6x-4 | | 8+9p+4(11-2p)= | | 40x+10(1.5x)=1500 | | -10n-3+2(5+6n)= | | .33(x-21)=.66 | | x+2+3x-4+2x+6= | | -2=b-150 | | 7+n=-8 | | 9.5-0.315x^2+0.743x=0 | | 2x-13=-81 | | 7-0.33333n=-28 | | 7-0.33333=-28 | | 46.5=3(4+5x) | | 2n+25=45 | | 48=5x+18 | | 2x-3+5(5x+2)= | | 10-3n=12 | | V-5/8=-1/4 | | 3n-10=12 | | f(x)=x^6/(2lnx) | | 32a^3-24a^2+36a=0 | | 1/x=-27/28 | | 80+13x=145 | | z/5-6=10/3 | | -7(v+2)=-4v-44 | | 3.53x+100=12.4609+10x | | -8h-8(2-4h)= |

Equations solver categories